2000
DOI: 10.1177/107110070002100610
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Plantar Fasciotomy for Chronic Heel Pain

Abstract: The purpose of our study was to determine whether endoscopic plantar fasciotomy is a safe and effective operation in this patient population. We reviewed our surgical results following endoscopic plantar fasciotomy in sixteen patients (twenty feet) with an average preoperative duration of symptoms of four years. Of the 20 feet, 9 had complete relief of pain while symptoms were improved in nine feet. One patient with bilateral symptoms had no relief in either foot. The average AOFAS hindfoot score improved from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
42
0
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(48 citation statements)
references
References 19 publications
4
42
0
2
Order By: Relevance
“…We can report equivalent results to those found by O'Malley, 8 using an endoscopic technique of partial release of the plantar fascia. The vast majority of patients reported satisfaction with the operation and no long-term surgical complications, lending further support to this technique as being safe and effective.…”
Section: Introductionsupporting
confidence: 80%
“…We can report equivalent results to those found by O'Malley, 8 using an endoscopic technique of partial release of the plantar fascia. The vast majority of patients reported satisfaction with the operation and no long-term surgical complications, lending further support to this technique as being safe and effective.…”
Section: Introductionsupporting
confidence: 80%
“…[11][12][13][14][15] The arthroscopic approach for the plantar fascia includes either a superficial fascial dry technique (without arthroscopic fluid lavage), by use of a slotted or transparent cannula similar to the arthroscopic carpal tunnel release (the arthroscope is located between the skin and the fascia), [11][12][13] or a deep fascial technique with arthroscopic fluid lavage (the arthroscope is located deep in the fascia). 14, 15 Komatsu et al 15 reported that the deep fascial approach for plantar fasciitis allows a wide visual field and working space.…”
Section: Discussionmentioning
confidence: 99%
“…Plantar fascia tension was directly proportional to Achilles tendon tension in cadavers in dynamic gait stimulator, so, Proximal Medial Gastrocnemius Release (PMGR) is an option in the treatment of chronic plantar fasciitis [15]. However, this technique has some complications.…”
Section: Discussionmentioning
confidence: 99%